Early and late results of carotid endarterectomy: retrospective study of 70 operations - Aguiar, Eduardo Toledo de (2001)
CONTEXT: Indications and results of carotid endar- terectomy have been defined from clinical multi centric trials like the European Carotid Surgery Trialists, North-American Symptomatic Carotid Endarterectomy Trial and Asymptomatic Carotid Atherosclerosis Study. The patients included in these trials were highly selected, as were the surgeons performing the operations. Clinical practice is different but the same results should be achieved. OBJECTIVE: To study indications, technique, early and late results, and whether carotid endarterectomy has been performed in accordance with standards defined by multicentric trials. DESIGN: Retrospective case report study. SETTING: A tertiary care private hospital. PARTICIPAANNTTSS:: 57 patients, on whom 70 carotid endarterectomies were performed over a 10-year period. The median age was 66.4 ± 7.8 years; 43 (75.4%) were male, 41 (71.9%) hypertensive, 36 (63.1%)currents mokers and 24(21.0%)haddiabetes. Bilateral carotidstenosis was presentin 31(54.3%) patients,peripheralarterial oclusionsin 32(56.1%) and is chemiccardiopathyin 25(43.1%). All patients had had angiography and 41 (71.9%)had also had aduplex-scanofneckarteries.Cerebral imagingvia computerized tomography scanor magnetic resonance imaging was obtained for 36 patients. Patients were followed up over a period of o neto122 months. MAIN MEASUREMENTTSS: early and late post- operative death, early and late post-operative stroke, and recurrence of atheroma plaque and symptoms relative to carotid stenosis. RESULTS: There was one post-operative death (1.4%) caused by myocardial infarction and two early strokes (2.8%): a total complication rate of 4.2%. After 3 and 5 years, 95.4% and 81.3% of patients respectively were stroke-free and 72.8% and 67.3% were alive. There were four recurrences and two of them related tos troke. Forty-nine(70%) stenoses operated on were symptomatic. Brain infarction was detected in 59.2% of patients who underwent computerized tomography scan or magnetic resonance imaging. CONCLUSIONS: Carotid endarterectomy was done in accordance with international standards. The most frequent cause of late death was myocardial infarction, and recurrences were related to stroke. Patients should be followed up closely.